Cytoplasmic genome of Indian potato varieties and breeding lines vis a vis prospects in potato breeding. Issue 3 (March 2021) - Sood, Salej; Kumar, Ashwani; Singh, Baljeet; S, Sundaresha; Bhardwaj, Vinay
Abstract: Advances in research resulted in development of a simple, rapid and reliable multiplex PCR protocol for cytoplasm differentiation in potato. Applying this rapid technique, we assessed the cytoplasm diversity in 57 Indian potato varieties, 15 popular exotic varieties and 47 biotic stress resistance breeding parental lines using five DNA based markers. Results revealed that T is the predominant cytoplasm type followed by D in Indian and exotic potato varieties as well as parental lines. The proportion of T and D type cytoplasm was 77.2% and 19.3% and 73.3% and 20.0% in Indian and exotic varieties, respectively. A and W type were found in one variety each, while M and P were missing in Indian varieties. All the popular Indian table potato varieties have tuberosum type cytoplasm with few exceptions of varieties bred for biotic stress resistance namely Kufri Himalini, Kufri Girdhari, carrying demissum cytoplasm. Opposite was true for Indian processing cultivars with the exception of Kufri Chipsona 4, which had T type cytoplasm. Evaluation of biotic stress resistance breeding parental lines showed increasing use of D (34.0%) and W (12.8%) cytoplasm in comparison to previously bred varieties. Although D type cytoplasm is associated with late blight resistance and male sterility, all Indian cultivars with D type cytoplasm are not resistant to late blight, nor they all are male sterile. Male fertile D type cytoplasm and the cytoplasms showing good interaction between cytoplasmic and nuclear gene for agronomic traits should be incorporated in the parental lines. Efforts must also be done to diversify the cytoplasm of cultivated potato with at least semi-cultivated cytoplasm types. Abstract : Potato, cytoplasm, tuberosum, demissum, wild type, male sterility, disease resistance.